The benefit of telemedicine in obesity care. Issue 3 (23rd February 2022) - Kahan, Scott; Look, Michelle; Fitch, Angela
Abstract: It has been estimated that, by 2030, nearly 80% of adults in the United States will have pre‐obesity or obesity. Despite the continued rise in obesity prevalence and the difficulty for many affected patients to lose weight and maintain lost weight, the use of guideline‐supported treatments, including pharmacotherapy, intensive behavioral counseling, and bariatric surgery, remains low. There are many potential barriers to effective use of antiobesity treatments, including limited access to guideline‐supported obesity care (often driven by practical challenges, geographic barriers, limited insurance coverage, and high cost of care) and a dearth of specialists and comprehensive treatment teams. Driven in part by the COVID‐19 pandemic, the recent expansion of telemedicine offers unique opportunities to mitigate these factors. This review discusses the use of telemedicine to facilitate obesity treatment. Continued growth and utility of telemedicine for obesity care require further formative and experimental research to determine best practices, assess challenges for implementation, and evaluate long‐term outcomes, as well as proactive policy changes to promote ongoing use of telemedicine beyond the COVID‐19 pandemic. Abstract :